Seasonal influenza vaccination of healthcare workers: a narrative review - Michał Jacek Jędrzejek; Agnieszka Mastalerz-Migas (International Journal of Occupational Medicine and Environmental Health, 2021)
Influenza is an acute respiratory disease caused by the influenza virus which often occurs in outbreaks and epidemics worldwide. The World Health Organization recommends annual vaccination of healthcare workers (HCWs) against influenza, because most of them are involved in the direct care of patients with a high risk of influenza-related complications. Given the significance of the disease burden, a targeted literature review was conducted to assess issues related to influenza vaccination among HCWs. The primary aim of this review was to assess the incidence of influenza among medical personnel and healthcare-associated influenza, and to outline the benefits of influenza vaccination for patients and HCWs themselves. Vaccination of HCWs seems to be an important strategy for reducing the transmission of influenza from healthcare personnel to their patients and, therefore, for reducing patient morbidity and mortality, increasing patient safety, and reducing work absenteeism among HCWs. The benefits of influenza vaccination for their patients and for HCWs themselves are addressed in literature, but the evidence is mixed and often of low-quality. Int J Occup Med Environ Health. 2022;35(2):127–39